Preclinical evaluation of the veterinary drug “Amoxidev 15” for its use in surgical and obstetric practice - L.-M. Kostyshyn; R. Sachuk; Ye. Kostyshyn; O. Katsaraba (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2021)
Suspension for injection “Amoxidev 15” is prescribed to fur-bearing animals (mink, fox), dogs and cats for the treatment of respiratory diseases (tonsillitis, tracheitis, pneumonia, bronchitis, rhinitis, sinusitis, bronchopneumonia), digestive (gastritis, enteritis, enteritis). genitourinary systems (nephritis, urethritis, urocystitis, mastitis, metritis, agalactia), musculoskeletal system (arthritis, osteoarthritis, joint injuries, tendonitis, hoof lesions), skin and soft tissues (eczema, dermatitis) caused by sensitive drug by microorganisms, including colibacillosis, streptococcus, bronchopneumonia, etc. Toxicological evaluation of the veterinary drug “Amoxidev 15” under the conditions of acute and subacute toxicological experiments on a model of white rats. According to the results of an acute toxicological experiment with intragastric administration of the drug “Amoxidev 15” white rats DL50 could not be calculated because the death of laboratory animals was not detected within 14 days after administration. The maximum administered dose (in absolute weight of the drug) was 20000.0 mg/kg body weight, which allows to refer the drug to class VI toxicity of relatively harmless substances (DL50 > 15000 mg/kg body weight), and the degree of safety to class IV – low-hazard substances (DL50 > 5000 mg/kg). According to the results of an acute toxicological experiment with subcutaneous administration of the drug “Amoxidev 15” white rats DL50 could not be calculated because the death of laboratory animals was not detected within 14 days after administration, the maximum dose was 5000.0 mg/kg body weight, therefore, the drug “Amoxidev 15” when administered subcutaneously by toxicity can be classified as class VI substances relatively harmless (DL50 Subcut > 4500.0 mg/kg). When administered subcutaneously to white rats, the drug “Amoxidev 15” under conditions of subacute toxicological experiment in doses of 0.1–1.0 ml/kg does not cause hemo-, hepato- and nephrotoxic effects on the body of laboratory animals, although 3-day administration of the drug in a dose 1.0 ml/kg body weight caused an increase in the activity of hepatospecific enzymes ALT and AST by 12.5 and 11.1 % (P < 0.05), respectively, relative to the control, which was restored to the control level 7 days after cessation.